Feeling and reactions of underground nursing students some situations related to children' sexuality. - Ribeiro, Moneda Oliveira (Revista da Escola de Enfermagem da USP, 1989)
This work is an investigation which the author intends to obtain subsidies ons preparation of nursing students on children' sexuality to give nursing care to children and adolescents. The motivation to obtain these date came fron absence of participation of students when talking about this topic in class-room. This fact did not make possible to identify feelings and reactions of students to some situations relative to tope.